Entrepreneurs Can Know More Than They Can Tell: Conceptualizing and Measuring Tacit Entrepreneurial Knowledge - Wuytens, Nils; Schepers, Jelle; Vandekerkhof, Pieter; Voordeckers, Wim (Frontiers in Psychology, 2022)
Organizational knowledge components dominate research on tacit knowledge. In order to overcome this dominance, we introduce Tacit Entrepreneurial Knowledge (TEK). TEK is conceptualized as one’s experiential learning from past experiences and insights that result in tacit knowledge regarding entrepreneurship that is implicit, personal, and uncodified. We subsequently develop a set of scenarios to quantify TEK based on the situational judgment test approach. In the debate on tacit knowledge, our measurement is innovative and relevant, as previous research failed to uncover an individual's tacit knowledge in the context of entrepreneurship, despite its importance on various entrepreneurial processes. This study aspires to ignite research into TEK by demonstrating important research opportunities unlocked by our conceptualization and subsequent measurement, offering future researchers a wide range of avenues to uncover the black box of tacit knowledge in entrepreneurship.